TERAPI COGNITIF BEHAVIOUR THERAPHY BAGI INDIVIDU YANG MENGALAMI STRESS - M Kis M Kis; Syaddam Husein M; Masril Masril (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to provide intervention to teenagers who easily experience stress when facing problems in their daily lives. This stress behavior can be seen in his daily activities, he is irritable, anxious, restless, easily angry even over trivial things. The subject felt offended if he saw a friend whispering, the subject felt that he was the one being talked about, the subject once had a fight with a friend just because the friend accidentally nudged him while he was standing, the subject once fell unconscious like a person possessed because there was a problem with his mother. This habit disrupts social relations and it is not uncommon for the subject to become stressed and fall ill when he or she experiences a lot of problems. This behavioral therapy involves cognitive steps related to the influence of irrational beliefs about problems that always bother the mind. The cognitive therapy process can help subjects to understand certain cognitive problems in carrying out the actions necessary to fulfill commitments, as well as increase the individual's willingness to engage in more adaptive behavior. In this study, cognitive therapy ran for 8 meetings. With 7 steps which involve CBT counseling, writing a daily diary based on the ABC format of CBT theory and the last step is a relaxation technique. The result of cognitive therapy is that the subject can reduce and become aware of the cognitive distortions that have disturbed his social life so far